Four-year overall surgical mortality rate at Princess Marina Hospital, a tertiary hospital in Botswana - Nkhabe Chinyepi; Mpapho J. Motsumi; Samuel Rackara; Rashid Lwango; Getrude Kapinga; Karabo Ngwako; Maranatha Sentsho; Tefo Leshomo; Unami Chilisa; Elijah K. Lekgowe; Mogomotsi Binikwa; Pako Motlaleselelo (AOSIS, 2023)
Background: Improving surgical mortality rates is a global priority as they measure the success of surgical care systems. There is no data on Botswana's overall surgical mortality rate. Therefore, this study set out to evaluate the overall mortality rate in a surgical department at Princess Marina Hospital, a tertiary hospital in Botswana. Method: This study is a single-center quantitative and retrospective study conducted in the surgical department at Princess Marina Hospital from August 2016 to December 2019. The Department of Surgery at Princess Marina Hospital keeps a prospectively updated database for quality assurance, which started in August 2016. The study received ethical approval. We included all patients older than 12 years admitted to the surgical department. Our adults surgical wards admit patients who are older than 12 years. This study collected all mortality data and determined the overall mortality rate as a percentage of surgical admissions. Results: We retrieved 4660 admissions. The mean age was 56 (standard deviation=20.1). 66% (3083/4660) were operated. Out of the 4660 admissions, 267 deaths were registered, giving an overall mortality rate of 6%. The overall postoperative mortality rate was 3.63% (112/3083), and the non-operatively managed patient mortality rate 9.83% (155/1577). Overall, malignancies were the leading cause of death, at 49.1%(131/267), followed by trauma at 22.1% (59/267). Conclusions: The 4-year overall surgical mortality rate at Princess Marina Hospital was 6%. The mortality rate of the non-operatively managed patients was more than twice as high as the postoperative mortality rate. Overall, malignancies were the leading cause of death, followed by trauma.